Disseminated Combined Talaromyces marneffei and Enterococcus faecium Bloodstream Infection Presenting as Gastrointestinal Perforation in a Patient with CARD9 Gene Mutation - Liang H; Duan X; Li T; Hu L; Guo J (Infection and Drug Resistance)
Huicang Liang,1,* Xuehong Duan,2,* Teng Li,3 Liang Hu,3 Jian Guo3 1Department of Laboratory Medicine, Key Laboratory of Precision Medicine for Viral Diseases, Guangxi Health Commission Key Laboratory of Clinical Biotechnology, Liuzhou People’s Hospital, Liuzhou, People’s Republic of China; 2Department of Laboratory Medicine, The First People’s Hospital of Xianyang, Xianyang, People’s Republic of China; 3Department of Laboratory Medicine, Shanghai East Hospital, School of Life Sciences and Technology, Tongji University, Shanghai, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jian Guo; Liang Hu, Department of Laboratory Medicine, Shanghai East Hospital, School of Life Sciences and Technology, Tongji University, Shanghai, 200123, People’s Republic of China, Email guojian1110@126.com; hu740646282@sina.comAbstract: This study presents a case of Talaromyces marneffei combined with Enterococcus faecium bloodstream infection with gastrointestinal symptoms as the sole initial clinical manifestation.The patient is a resident of Shanghai and has no recent travel history to areas with a high risk of T. marneffei infection. He was admitted to the emergency room due to severe upper abdominal pain. Laboratory tests indicated elevated levels of white blood cells, rapid C-reactive protein, and procalcitonin, while the human immunodeficiency virus (HIV) test returned negative. An abdominal CT examination revealed gas and fluid accumulation in the abdominal cavity, raising suspicion for gastrointestinal perforation and peritonitis. Initially, he received symptomatic treatment for gastrointestinal perforation and abdominal infection, but his response to the treatment was poor.Through metagenomic next-generation sequencing (mNGS) and multiple blood cultures, a mixed infection of T. marneffei and E. faecium was identified in the patient’s blood. Combination treatment with vancomycin and amphotericin B was initiated to manage the symptoms. However, we discovered genome-wide exon CARD9 mutations in the patient, complicating the treatment process. Ultimately, the delayed diagnosis of T. marneffei resulted in the patient’s severe deterioration, rendering the anti-infective treatment ineffective, and leading to the patient’s death.This report underscores the challenges associated with diagnosing T. marneffei infections in non-AIDS patients and in non-endemic regions. The diagnosis of disseminated infections poses significant difficulties, particularly when mixed infections are present, complicating clinical treatment. This highlights the critical importance of standardized blood cultures for the early diagnosis of T. marneffei. Additionally, we must prioritize timely whole-genome testing to identify potential immune gene mutations.Keywords: Talaromyces marneffei, drug susceptibility, disseminated infection, HIV, CARD9 gene mutation, antifungal antibacterial therapy